2014
DOI: 10.1186/1477-7819-12-96
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of thoracic or lumbar patient-controlled epidural analgesia methods after thoracic surgery

Abstract: BackgroundWe aimed to compare patient-controlled thoracic or lumbar epidural analgesia methods after thoracotomy operations.MethodsOne hundred and twenty patients were prospectively randomized to receive either thoracic epidural analgesia (TEA group) or lumbar epidural analgesia (LEA group). In both groups, epidural catheters were administered. Hemodynamic measurements, visual analog scale scores at rest (VAS-R) and after coughing (VAS-C), analgesic consumption, and side effects were compared at 0, 2, 4, 8, 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…These results are in line with other studies, where no significant complications were observed with the exception of hypotension [17]. Another report demonstrated that complications such as hypotension, bradycardia, atelectasis, and need for ICU were observed but at a lower frequency in thoracic epidural analgesia compared to lumbar epidural analgesia [24]. A review of lung cancer surgical patients suggested that complications did occur following epidural analgesia, but there were no significant differences when comparing epidural with subpleural analgesia [25].…”
Section: Discussionsupporting
confidence: 87%
“…These results are in line with other studies, where no significant complications were observed with the exception of hypotension [17]. Another report demonstrated that complications such as hypotension, bradycardia, atelectasis, and need for ICU were observed but at a lower frequency in thoracic epidural analgesia compared to lumbar epidural analgesia [24]. A review of lung cancer surgical patients suggested that complications did occur following epidural analgesia, but there were no significant differences when comparing epidural with subpleural analgesia [25].…”
Section: Discussionsupporting
confidence: 87%
“…Some consideration must be made to the impact on early ERAS goals and how they will be achieved, and expert post-operative input may be required to ensure reliable analgesia. Although epidurals sited in the lumbar spine have an evidence base for analgesic benefit in gynecologic surgery, thoracic epidurals are preferred: epidurals should be sited at the level appropriate for innervation of the surgical area, and thoracic epidurals are likely to cause less hypotension [ 67 ] and motor block [ 68 ] than those in the lumbar segments.…”
Section: Postoperative Analgesiamentioning
confidence: 99%
“…[ 21 ] EA-induced hypotension was reported in the patients with multiple fracture ribs by Sagiroglu et al . [ 31 ] and Peek et al . [ 32 ] ESPB is considered a simpler, safer, and less invasive regional analgesic technique that provides extensive truncal analgesia with smaller risk of pneumothorax or neurovascular injury as there are no vital structures near the site of needle insertion.…”
Section: Discussionmentioning
confidence: 99%